Improving Student Knowledge on Selected History Topics through Tiktok Platform as Digital Learning Tool - Shelly April Decenilla; Rona C. Apolinario; Zaldy T. Cuaton; Cathyleen Clarido (Journal of Digital Learning and Education, 2022)
According to several studies, many students perceive History as rigid, static, and boring because of its reliance on narration pedagogy, limiting their ability to develop critical-thinking abilities. To address the issue, the researchers applied utilization of Self-made mini-lecture Tiktok videos as intervention to enhance the knowledge of thirty-three (33) second year Education students in selected topics in their history course subject. After 5 weeks duration of implementation phase, results unveiled that students’ knowledge in selected history topics were improved as data showed that the knowledge gained by students were analysed as comprehensive and reflective, compared to their knowledge in pre-intervention that were categorized as general and lack of knowledge. In this regard, students demonstrated that using self-made mini-lecture Tiktok video has positive influence on students' learning behavior by triggering their desire to learn in order to gain confidence in educating their audience while making learning history fun and entertaining.